Relief carvings of geometric, flora, and fauna motifs - Temples of India Project Team (Jio Institute, 2024)
Broken debris from the original temple assembled on the southeast face of the adhisthana (elevation of the first tier). U-shaped rounded stones are assembled on the parapet (their position or purpose in the original temple is unknown). Relief carvings of geometric, flora, and fauna motifs feature all around the adhisthana.